Ocena sytuacji finansowej gminy Poraj w latach 1999-2003 w aspekcie działalności inwestycyjnej - Ławińska, Olga (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The present article intended to show how the local authorities of Poraj realized communal investments in 1999-2003 from social and economic viewpoints. At the beginning the geographic and economic potential of Poraj are described. The next part presents the structure of local communities incomes and expenditures. Various aspects, such as the willingness to investments, local conditions of life, the development of the region are taken into consideration. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 557-564